2017
DOI: 10.1504/ijtel.2017.10005186
|View full text |Cite
|
Sign up to set email alerts
|

The development of the reflective practitioner through digital storytelling

Abstract: This paper presents a multiple case study on the use of digital storytelling to support the development of reflection and digital skills in professional education. Students from two universities, one group studying health and social care, the other training to be teachers, were asked to produce two artefacts, at the beginning and end of their respective modules, in which they reflected on the aspects of professional and personal learning. The artefacts, some of which were produced in groups, others by individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…From Lambert's (2009) classification of digital stories, here we focus on stories about people's activities and, specifically, those related to students' professional activities and social commitments involved in the construction of their professional identities. As for the use of tools in the creation of the digital story, there is now available a wide range of Web 2.0 tools and applications offering vast opportunities in the field of education while requiring minimal or no additional expertise in their use (Asing-Cashman, Gurung, Limbo & Rutledge, 2014;Challinor, Marín & Tur, 2017).…”
Section: The Role Of Technology In Health and Social Care And Teachermentioning
confidence: 99%
See 2 more Smart Citations
“…From Lambert's (2009) classification of digital stories, here we focus on stories about people's activities and, specifically, those related to students' professional activities and social commitments involved in the construction of their professional identities. As for the use of tools in the creation of the digital story, there is now available a wide range of Web 2.0 tools and applications offering vast opportunities in the field of education while requiring minimal or no additional expertise in their use (Asing-Cashman, Gurung, Limbo & Rutledge, 2014;Challinor, Marín & Tur, 2017).…”
Section: The Role Of Technology In Health and Social Care And Teachermentioning
confidence: 99%
“…At the presentation of the task in class, students were told that the resulting posted artefacts would be analysed for research aims and that they were free to delete the artefacts when the assessment was concluded and for this reason 3 artefacts in TE were missing. The possibilities of digital artefacts for storytelling have been analysed in previous work (Challinor, Marín & Tur, 2017;Tur, Challinor & Marín, 2016): It has been observed that students improved their digital skills by exploring the possibilities of OER (Open Educational Resources), developing multimedia communicative skills and empowering creativity.…”
Section: The Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a rich body of literature about the educational use of DST, particularly from a constructivist approach (Wu & Chen, 2020), since it has been used to engage students in their learning progress as an expression of their own identity (Kortegast & Davis, 2018), be it in the mainstream classroom (Tur et al 2017) or in some specific area related with different minorities (Anderson & Mack, 2019). Creativity has been the object of study in most cases, for example Schmoelz (2018) examined student interaction in classroom activities that adopted DST to enable co-creativity, highlighting its positive impact on factors such as engagement, control, shared enjoyment and fun.…”
Section: Dst In Education and Teacher Training Programsmentioning
confidence: 99%
“…Training and development are influenced by two mechanisms such as exchanging stories and engagement in dialogues to achieve a shared life story and an organizational identity. Strategic leaders stimulate training and development with the promotion of new ideas, thoughts and assumptions, collective action and intra and extra organizational dialogue (Tur et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%